A reserva legal no cerrado sensu stricto: benefícios quanto à sua implementação, restauração e uso econômico - Moura, Mariana Lima (2016)
The publication of Federal Law n o 12,651 of 2012 has rendered many changes for the rural property concerning the regularization of the Legal Reserve. The entire rural property must be registered in the Rural Environmental Registry, which will allow the Federal and State governments to know and map the remaining native vegetation in the territory. The Environmental Regularization Program will allow rural landowners to choose, among others, the adherence to the legal reserve recomposition, by means of planting native or exotic species. In Minas Gerais, Brazil, the law specifies 20% of the property destined to Legal Reserve, since the Biomes present in the state’s territory are the Atlantic Forest, Caatinga and Cerrado. Of these biomes, this research highlights the Cerrado, considered a hotspot that presents an immensely rich flora, which can be used for a large variety of economic uses. In this sense, this work approaches the technical and legal aspects of the Legal Reserve, as well as its environmental regularization and the implications for ecological restauration, focusing on the economic use of the area. We identified the main uses and soil occupation in the Cerrado biome in Minas Gerais, as well as the main impacting activities. We surveyed the main species of the biome, indicated for ecol ogical restauration in sensu stricto phytophisiognomy, aiming at future exploration of the area. For choosing the method indicated for ecological restauration, a decision-making matrix was elaborated according to the diagnosis of the area to be used as Legal Reserve. In conclusion, the Environmental Regularization Program might allow the rural landowner, in addition to fulfilling the law, the possibility to adhere to the recomposition, which can later generate income for the property. In addition, this research can subsidize the elaboration of a technical bulletin destined to the rural landowner, regarding the Legal Reserve in the Environmental Regularization Program.